Empirical model of Poynting flux derived from FAST data and a cusp signature. Issue 1 (8th January 2014) - Cosgrove, Russell B.; Bahcivan, Hasan; Chen, Steven; Strangeway, Robert J.; Ortega, Juan; Alhassan, Mohamed; Xu, Yuchen; Welie, Megan Van; Rehberger, James; Musielak, Sebastian; Cahill, Nicole
<x xml:space="preserve">Abstract</x> [1] Empirical models of the Poynting flux and particle kinetic energy flux, associated with auroral processes, have been constructed using data from the FAST satellite and are available online. The models output flux maps as a function of several geophysical parameters: (1) clock angle of the interplanetary magnetic field (IMF), (2) magnitude of the IMF in the GSM y‐z plane, (3) solar wind speed, (4) solar wind number density, (5) magnetic dipole tilt angle, and (6) the AL index (optional for Poynting flux). The choice of parameters is motivated by the Weimer potential model. Because the Poynting flux distribution has a heavy tail, care must be taken in applying the model to events that may be uncommon, and the model output includes a measure of quality based on the density of FAST orbits in the parameter space. The models are constructed by fitting the data to a sum of empirical orthogonal functions (EOFs), with coefficients modeled by quadratic equations in the geophysical parameters. The EOFs are constructed from the same data set using singular value decomposition, along with a smoothing/interpolation algorithm that minimizes curvature and incorporates uncertainty. Potential applications include specification of the auroral energy input for general circulation models. Basic findings from the model include verification of the importance of the auroral electrojets as features of auroral Poynting flux deposition and identification of the cusp as a third important feature. The cusp makes an important contribution to the overall energy budget when the IMF is north of ±90°.